Lamellar Body Count has Higher Sensitivity and Specificity in the Prediction of Neonatal Respiratory Distress Syndrome - Aryando Pradana (Indonesian Journal of Obstetrics and Gynecology, 2012)
Objective: The study was designed to acquire the cut-off value for lamellar body count and its role in predicting the presence of Respiratory Distress Syndrome (RDS) in pregnancy with gestational age above 28 weeks. Method: Amniotic fluid specimens were collected by amniotomy during cesarean section from women with gestational age above 28 weeks. A haematology analyzer (Advia 120) was used to determine the lamellar body counts. We also performed foam stability test and observed the development of respiratory distress syndrome. Receiver operating characteristics curve was estimated to assess the threshold of lamellar bodies count that may predict the presence of Respiratory Distress Syndrome. Result: Fifty nine specimens were collected from woman with 29 - 42 weeks gestational age. The incidence of Respiratory Distress Syndrome was 15.3%. Area under the curve for lamellar body count was 0.94. Lamellar body count, with the best cut-off point of 50,000 cell/Î¼l had sensitivity 89% and specifity 92% for predicting the presence of RDS, while the sensitivity of foam stability test was 67% and specificity was 90%. The negative predictive value of the lamellar body count was 98% slightly better than the negative predictive value of the foam stability test 94 %. Conclusion: Although both test are good predictor of RDS, lamellar body count has higher sensitivity and specificity. It also has more advantages as it only requires small amount of sample, fast, easy and more objective. [Indones J Obstet Gynecol 2012; 36-4: 176-80] Keywords: foam stability test, lamellar body, respiratory distress syndrome